Food allergy in primary care: Management of food allergy - Caimmi, Davide; Caffarelli, Carlo; Licari , Amelia; Miraglia Del Giudice, Michele; Calvani, Mauro; Marseglia, Gian Luigi; Marseglia, Alessia; Ricci, Giampaolo; Martelli, Alberto; Cravidi, Claudio; Caimmi, Silvia (Acta Biomedica Atenei Parmensis, 2021)
Prevalence of food allergy has been increasing over the last decades. It may appear as an immediate or a delayed reaction. The disease has a major impact on the quality of life of patients and their families, and it is associated to elevated costs. Primary care physicians are the first healthcare providers who assist children with food allergy, especially in mild to moderate forms. Through the present review, we examine the steps that should be followed in primary care to manage food allergy, and to promptly prescribe an elimination diet and an emergency kit in case of accidental exposure to the allergen. We also focus on the special management of IgE and non-IgE mediated cow’s milk allergy, and on management and prevention of egg and peanuts allergy.